Risk factors for suicidal attempts in a sample of outpatients with treatment-resistant depression: an observational study - Civardi, Serena Chiara; Besana, Filippo; Carnevale Miacca, Giovanni; Mazzoni, Filippo; Arienti, Vincenzo; Politi, Pierluigi; Brondino, Natascia; Olivola, Miriam (Frontiers in psychiatry, 2024)
Treatment-resistant depression (TRD) is commonly defined as the failure of at least two trials with antidepressant drugs, given at the right dose and for an appropriate duration. TRD is associated with increased mortality, compared to patients with a simple major depressive episode. This increased rate was mainly attributed to death from external causes, including suicide and accidents. The aim of our study is to identify socio-demographic and psychopathological variables associated with suicidal attempts in a sample of outpatients with TRD. We performed a monocentric observational study with a retrospective design including a sample of 63 subjects with TRD referred to an Italian outpatient mental health centre. We collected socio-demographic and psychopathological data from interviews and clinical records. 77.8% of the sample (N=49) were females, the mean age was 49.2 (15.9). 33.3% (N=21) of patients had attempted suicide. 54% (N=34) of patients had a psychiatric comorbidity. Among the collected variables, substance use (p=0.031), psychiatric comorbidities (p=0.049) and high scores of HAM-D (p=0.011) were associated with the occurrence of suicide attempts. In the regression model, substance use (OR 6.779), psychiatric comorbidities (OR 3.788) and HAM-D scores (OR 1.057) were predictive of suicide attempts. When controlling for gender, only substance use (OR 6.114) and HAM-D scores (OR 1.057) maintained association with suicide attempts. The integrated treatment of comorbidities and substance abuse, which involves different mental health services, is fundamental in achieving the recovery of these patients. Our study supports the importance of performing a careful clinical evaluation of patients with TRD in order to identify factors associated with increased risk of suicide attempts.